2016
DOI: 10.21857/yq32ohq339
|View full text |Cite
|
Sign up to set email alerts
|

Is there a trade-off between clutch size and egg volume in Magpie Pica pica in northwestern Croatia?

Abstract: A negative relationship, or trade-off, between egg size (egg volume or egg mass) and clutch size is a central component of life-history theory. This paper presents evidence for a relationship between clutch size and egg volume (egg size) of the Magpie (Pica pica). Magpies are common and sedentary birds in study area. Egg characteristics were recorded in Mokrice rural area (46°00'N, 15°55'E), northwestern Croatia; carried out during the breeding season (April-May) in the year 2012. I have not detected any negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Saches-Lafuente 2004) and some positive (e.g. Dolenec, 2016b). Clutch size and egg size (volume) values of the Eurasian wryneck in this study are similar to the results collected in other European countries.…”
Section: Results and Discusionsupporting
confidence: 89%
“…Saches-Lafuente 2004) and some positive (e.g. Dolenec, 2016b). Clutch size and egg size (volume) values of the Eurasian wryneck in this study are similar to the results collected in other European countries.…”
Section: Results and Discusionsupporting
confidence: 89%
“…According to Hõrak et al (1995), "being hatched from a large egg could potentially be beneficial of the laying female, however, high investment into egg quality (size) might conflict with her own energetic demands and willingness to produce more offspring". Studies have found negative (Martin et al 2006, Bańbura et al 2018, positive (Aslan & Yavuz 2010, Dolenec 2016) and no significant correlations (Dolenec 2011, Bao et al 2020 between egg size and clutch size. Negative relationships between egg volume (or egg mass) and clutch size is consequence of compromise between egg size and clutch size with females laying numerous small or few large eggs (e.g.…”
Section: Introductionmentioning
confidence: 96%